Protective Effect of Nicorandil on Cardiac Microvascular Injury: Role of Mitochondrial Integrity. (5th July 2021) - Jiang, Xiaosi; Wu, Dan; Jiang, Zichao; Ling, Weiwei; Qian, Geng
Abstract : A major shortcoming of postischemic therapy for myocardial infarction is the no-reflow phenomenon due to impaired cardiac microvascular function including microcirculatory barrier function, loss of endothelial activity, local inflammatory cell accumulation, and increased oxidative stress. Consequently, inadequate reperfusion of the microcirculation causes secondary ischemia, aggravating the myocardial reperfusion injury. ATP-sensitive potassium ion (KATP ) channels regulate the coronary blood flow and protect cardiomyocytes from ischemia-reperfusion injury. Studies in animal models of myocardial ischemia-reperfusion have illustrated that the opening of mitochondrial KATP (mito-KATP ) channels alleviates endothelial dysfunction and reduces myocardial necrosis. By contrast, blocking mito-KATP channels aggravates microvascular necrosis and no-reflow phenomenon following ischemia-reperfusion injury. Nicorandil, as an antianginal drug, has been used for ischemic preconditioning (IPC) due to its mito-KATP channel-opening effect, thereby limiting infarct size and subsequent severe ischemic insult. In this review, we analyze the protective actions of nicorandil against microcirculation reperfusion injury with a focus on improving mitochondrial integrity. In addition, we discuss the function of mitochondria in the pathogenesis of myocardial ischemia.